EFFECT OF MOISTURE CONTENTS AND COMPRESSION AXES ON SOME PHYSICAL AND MECHANICAL PROPERTIES OF DIOCLEA REFLEXA SEED - Olakunle OLUKAYODE; Eyitope Israel ALADE; Seun OYELAMI (Journal of Applied Life Sciences and Environment)
Interest in unconventional seeds such as Dioclea reflexa is growing in the tropical regions, with the potential for utilisation as food or industrial materials. Researchers confirmed that Dioclea reflexa seed has the potential for clinical use, use as a food source, and as industrial raw material. This research studies the effect of moisture content on the physical properties of Dioclea reflexa seed and the effect of moisture content and compression axes its mechanical properties. Standards methods were used to determine the physical properties, while the mechanical properties were derived from force-deformation curves for the moisture content range 4.8 to 12.1% (wet basis). The mean values of the seed’s length increased by 3.55% (from 31.01 mm), the width increased by 4.13% (from 26.64 mm), and the thickness decreased by 2.48% (from 21.75 mm). The geometric mean diameter increased by 1.68%, surface area increased by 3.68%, sphericity decreased by 1.54% and individual seed mass increased by 10.46%. The physical properties exhibit linear relationships with moisture content. Rupture force increased by 75% (from 0.80 kN) for loading along the major axis; by 84% (from 0.72 kN) for the intermediate axis; and by 41% (from 0.78 kN) for the minor axis. Rupture energy increased from 0.18 J to 1.25 J for compression along the major axis, from 0.087 J to 0.43 J for the intermediate axis, and from 0.080 J to 0.18 J for the minor axis. The mechanical properties were found to be moisture content and loading orientation-dependent. Reducing moisture content reduced both the force and the energy required to rupture the seeds. The data generated will be useful in the design of processing machinery and storage facilities for the seeds.